Typical Profiles and Distributions of Plasma and Magnetic Field Parameters in Magnetic Clouds at 1 AU - Rodriguez, L. (2016)
Magnetic clouds (MCs) are a subset of interplanetary coronal mass ejections (ICMEs). They are important because of their simple internal magnetic field configuration, which resembles a magnetic flux rope, and because they represent one of the most geoeffective types of solar transients. In this study, we analyze their internal structure using a superposed epoch method on 63 events observed at L1 by the Advance Composition Explorer (ACE), between 1998 and 2006. In this way, we obtain an average profile for each plasma and magnetic field parameter at each point of the cloud. Furthermore, we take a fixed time-window upstream and downstream from the MC to also sample the regions preceding the cloud and the wake trailing it. We then perform a detailed analysis of the internal characteristics of the clouds and their surrounding solar wind environments. We find that the parameters studied are compatible with log-normal distribution functions. The plasma β and the level of fluctuations in the magnetic field vector are the best parameters to define the boundaries of MCs. We find that one third of the events shows a peak in plasma density close to the trailing edge of the flux ropes. We provide several possible explanations for this result and investigate if the density peak is of a solar origin (e.g. erupting prominence material) or formed during the magnetic cloud travel from the Sun to 1 AU. The most plausible explanation is the compression due to a fast overtaking flow, coming from a coronal hole located to the east of the solar source region of the magnetic cloud.